Correlation Between Emotional Intelligence and Critical Thinking Disposition Among Undergraduate Saudi Nursing Students - Abdalhadi Hasan; Hala Noor (SAGE Publishing, 2024)
Introduction Thinking skills are important concepts that have been discussed by various researchers. Improving and enhancing students' thinking skills has become a fundamental goal of educational systems. There are several methods used to promote inclusive critical thinking in individuals. Objectives This study aimed to assess the correlation between emotional intelligence (EI) and critical thinking disposition skills in undergraduate Saudi nursing students. Methods This descriptive correlational study design used a convenience sample of 300 undergraduate nursing students. The respondents were selected from King Khaled University. The study utilized the Schutte Self-Report Emotional Intelligence Test (SSEIT) and the Critical Thinking Disposition Scale (CTDS). Results The results demonstrated a positive correlation between the two variables ( r  = .60, p  < .001). The variables differed among the nursing students depending on their academic year of study ( F  = 52.000, p  < .001). Conclusions In conclusion, higher levels of EI and critical thinking skills in nursing students are associated with improved problem-solving skills and better judgment, which contribute to the future development of EI and critical thinking nursing professionals.